Natural Concurrent Infections with Black Spot Disease and Multiple Bacteriosis in Farmed Nile Tilapia in Central Kenya - Daniel W. Wanja; Paul G. Mbuthia; Robert M. Waruiru; Lilly C. Bebora; Helena A. Ngowi (Veterinary Medicine International)
Nile tilapia (Oreochromis niloticus) is the most cultured and available fish for Kenyan consumers, and therefore, any tilapine disease deprives them the valuable source of protein. Nile tilapia farm was diagnosed with severe concurrent black spot disease and multiple bacteriosis using gross lesions and parasitological, histopathology, and standard bacteriological procedures. A total of 25 fish were sampled and inspected, and all of them had raised, macroscopic 1 mm-sized black spot lesions. The mean intensity of black spots per fish was 728 with an abundance of 2–1740 metacercariae cysts per fish. A high intensity of black spot infestation was observed in the fins (43.9%), skin and underlying muscles (18.3%), and gills (18%). In addition, histopathological data confirmed presence of a metacercaria of Neascus spp. as the aetiological agent of black spot disease. Furthermore, a thick fibrous capsule around the metacercaria, black pigment melanomacrophages, and moderate muscle atrophy were observed. The most prevalent bacteria isolated were Aeromonas, Enterobacter cloacae, Klebsiella pneumoniae, and Micrococcus luteus. Physicochemical parameters of pond water were temperature (28.2°C), dissolved oxygen (4.2 mgl−1), pH (8.5), ammonia free nitrogen (15.8 mgl−1), alkalinity (112 mgl−1), hardness (68 mgl−1), nitrites (0.058 mgl−1), nitrates (58 mgl−1), and phosphates (0.046 mgl−1). However, the levels of nitrates, nitrites, alkalinity, and ammonia free nitrogen exceeded the recommended limits. In conclusion, these findings suggest that coinfections by these organisms coupled by water quality-related stress can be associated with low-grade mortality observed in postfingerling tilapia as well as reduced growth. The authors recommended immediate destocking, thorough disinfection, and control of piscivorous birds. Moreover, attention ought to be geared towards prevention of parasitic infestations in fish so as to minimize fish deaths related to secondary bacteriosis. Further experimental studies should be carried out to elucidate the relationship of these pathogens.